2014
DOI: 10.1101/005397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differences in sensitivity to EGFR inhibitors could be explained by described biochemical differences between oncogenic Ras mutants

Abstract: Emerging data suggest different activating Ras mutants may have different biological behaviors. The most striking example may be in colon cancer, where activating KRAS mutations generally indicate a lack of benefit to treatment with EGFR inhibitors, although the activating KRAS G13D mutation appears to be an exception. As KRAS G13D generally shares the same biochemical defects as the other oncogenic KRAS mutants, a mechanism for differential sensitivity is not apparent. Here, a previously developed mathematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Of note, oncogenic mutants at codon 12, 13, and 61 are biochemically similar [23]. However, there are subtle differences between different oncogenic mutants that, in some cases, can have large effects [11,24]. For that reason, we extended the model to include G12C by incorporating recently published data [25].…”
Section: Model Extension To Include Protein Turnover and The G12c Mutantmentioning
confidence: 99%
“…Of note, oncogenic mutants at codon 12, 13, and 61 are biochemically similar [23]. However, there are subtle differences between different oncogenic mutants that, in some cases, can have large effects [11,24]. For that reason, we extended the model to include G12C by incorporating recently published data [25].…”
Section: Model Extension To Include Protein Turnover and The G12c Mutantmentioning
confidence: 99%
“…We also have revealed that the sensitivity of KRAS G12C cells to the EGFR inhibitor cetuximab has a similar mechanism as what we recently demonstrated for KRAS G13D and its response to cetuximab (14). For the KRAS G13D study, we first used mathematic modeling of available biochemical detect to predict a priori that reductions in wild-type RAS explained the response of KRAS G13D CRC to EGFR inhibition (17). In contrast, for this study we first identified KRAS G12C CRC as a genotype that was sensitive to EGFR inhibition empirically, and then we used our mathematical model to evaluate whether the observed deficiencies in the binding of KRAS G12C to NF1 and CRAF, as well as the dependency on the number of KRAS alleles mutated, were consistent with the known mechanisms of RAS signal regulation.…”
Section: Discussionmentioning
confidence: 76%
“…Our previous finding that EGFR inhibitors like cetuximab can reduce WT HRAS-GTP and NRAS-GTP in KRAS G13D CRC cells was first uncovered by our mathematical modeling (17). Our mathematical model of oncogenic RAS signaling was developed to be capable of modeling specific RAS mutant alleles on the basis of their kinetic, equilibrium, and enzymatic biochemical parameters for the reactions that regulate RAS-GTP cycling (18)(19)(20).…”
Section: Modeling Supports Ras Signaling Complex Observationsmentioning
confidence: 99%
“…We have previously used modeling to address specific questions pertaining to RAS mutants G12D, G12V, F28L, G12C, and G13D [8,15]. Here, an extension of the number of mutants studied was undertaken to develop intuition for how a collection of related, but distinct, pathological mutants might behave.…”
Section: Discussionmentioning
confidence: 99%
“…Our original RAS model focused on the oncogenic G12D and G12V mutants, as well as fast-cycling F28L mutant [8]. To study problems pertaining to specific RAS mutants important to cancer, we have since extended our model to include G13D, Q61L, Q61K, Q61W, Q61H, Q61P, and Q61R [15] and G12C. We here extend our model to an additional 6 oncogenic mutations: G12R, G12P, G13S, G13V, A59T, and 10dupG, yielding a total of 16 different oncogenic mutants We considered the case where all of the RAS in the cell is mutated (Figure 3A,B).…”
Section: Expansion Of the Model To Additional Oncogenic Mutantsmentioning
confidence: 99%